Influência da ingestão crônica de gordura vegetal hidrogenada sobre aspectos bioquímico-moleculares no estriado de ratos expostos a um modelo animal de mania - Dias, Verônica Tironi (2015)
Taking into account the unknow etiology of neuropsychiatry disturbances, including bipolar disorder (BD) and the bad eating habbits, the purpose of this study was to evaluate the influence of chronic consumption of trans fat, remaining in a large amount in processed foods, on lipid composition of striatal membranes, as well as its biochemical-molecular alterations in this tissue. To perform this study, a second generation of male rats born from mothers and grandmothers supplemented with soybean oil (SO-C, an isocaloric control group) or hydrogenated vegetable fat (HVF, rich in TFA) (3 g/kg; p.o.) since gestational period until adulthood was used. They were kept under oral treatment until adulthood, when they were exposed to an AMPH-induced model of mania (4 mg/Kg/ml/day, i.p., during 14 days). The HVF group presented 0.38% of TFA incorporation in the striatum, affecting Na+/K+ ATPase enzyme activity, which was decreased per se and following AMPH-exposure. The HVF group also showed increased protein carbonyl (PC) and brain-derived neurotrophic factor (BDNF) mRNA levels after AMPH administration, while these oxidative and molecular changes were not observed in the other experimental groups. Additionally, a negative correlation between striatal Na+/K+ ATPase activity and PC levels (r2= 0.49) was observed. The prolonged consumption of HVF, rich in TFA, allowed that FA incorporation and increases striatal oxidative status, thus impairing the functionality of Na+/K+ATPase and affecting molecular targets as BDNF mRNA. We hypothesized that the chronic intake of processed foods (rich in TFA) facilitates the development of neuropsychiatric diseases, particularly the bipolar disorder.